Potential Role of Exercise Induced Extracellular Vesicles in Prostate Cancer Suppression - Zhang, Ying; Kim, Jin-Soo; Wang, Tian-Zhen; Newton, Robert U.; Galvão, Daniel A.; Gardiner, Robert A.; Hill, Michelle M.; Taaffe, Dennis R. (Frontiers in Oncology, 2021)
Physical exercise is increasingly recognized as a valuable treatment strategy in managing prostate cancer, not only enhancing supportive care but potentially influencing disease outcomes. However, there are limited studies investigating mechanisms of the tumor-suppressive effect of exercise. Recently, extracellular vesicles (EVs) have been recognized as a therapeutic target for cancer as tumor-derived EVs have the potential to promote metastatic capacity by transferring oncogenic proteins, integrins, and microRNAs to other cells and EVs are also involved in developing drug resistance. Skeletal muscle has been identified as an endocrine organ, releasing EVs into the circulation, and levels of EV-containing factors have been shown to increase in response to exercise. Moreover, preclinical studies have demonstrated the tumor-suppressive effect of protein and microRNA contents in skeletal muscle-derived EVs in various cancers, including prostate cancer. Here we review current knowledge of the tumor-derived EVs in prostate cancer progression and metastasis, the role of exercise in skeletal muscle-derived EVs circulating levels and the alteration of their contents, and the potential tumor-suppressive effect of skeletal muscle-derived EV contents in prostate cancer. In addition, we review the proposed mechanism of exercise in the uptake of skeletal muscle-derived EVs in prostate cancer.